FBG sensors for process and structural health monitoring of a small type III composite overwrapped pressure vessel for unmanned aerial vehicle - Rocha, Helena Cristina Lopes (2022)
In this work, fibre Bragg grating (FBG) sensors were embedded in a 1-litre type III composite overwrapped pressure vessel (COPV) for an unmanned aerial vehicle (UAV), during its manufacturing for process and structural health monitoring (SHM). A single optical fibre having eight FBG sensors was fixed around an aluminium liner to form a grid network. The carbon fibre/epoxy composite layers were wound on top of it with a winding machine. The FBG sensors were able to follow the developed strain during winding, making it an important quality control tool. The same sensors were used to monitor impact tests, where the distances between real and predicted locations varied between 17 and 56 mm.